Listeria Endophthalmitis Cured With Linezolid in an Immunocompetent Farmer Woman: Hazard of a Sweep of a Cow's Tail. (23rd October 2019) - Lécuyer, Romain; Boutoille, David; Khatchatourian, Lydie; Ducloyer, Jean-Baptiste; Gibaud, Sophie; Raffi, François; Gaborit, Benjamin
Abstract: We report the first case of an unexpected exogenous Listeria monocytogenes endophthalmitis in a previously healthy woman after a cow's tail's sweep, successfully treated with surgery and linezolid. It is the first case carried out with linezolid to treat Listeria endophthalmitis. Therefore, it may challenge the requirement for intravenous antibiotics for long-term treatment.